O Programa Residência Pedagógica na Universidade Federal de Alfenas: a experiência do docente orientador no contexto aa Pandemia de Covid-19 - Santos, Ana Carolina Sabino Dos (2024)
This research investigates the orientation of pedagogical practice in the context of teacher education, focusing on the Pedagogical Residency Program (PRP) and the role of Teaching Advisors. These teacher-educators, affiliated with the Higher Education institution, play a crucial role in guiding teacher candidates during their immersion in schools, integrating the residency experience with the theoretical and practical foundations of the teaching profession. Thus, the central objective of this research was to analyze the experience of teaching advisors in the development of the PRP at the Federal University of Alfenas (UNIFAL-MG), as well as to understand the didactic-pedagogical movement of the teaching advisor during the COVID- 19 pandemic. The research was qualitative, with data collected through semi-structured interviews with seven teaching advisors from UNIFAL-MG who participated in the program during the validity period of Edital no 1 of 2020. The interviews were analyzed through constructive-interpretative analysis. The interpretative analysis of the data revealed three cores of meaning: I) Teaching in times of pandemic in the Pedagogical Residency; II) The student- teacher relational dimension; III) The exercise of teaching and digital mediation. The results highlight that the experience of advisors in the PRP during the pandemic was marked by challenges and learning. The adaptation of subprojects for remote teaching faced various obstacles, emphasizing the particularities of each subproject and the limitations encountered. The movement to adapt subprojects to remote teaching was not uniform and faced challenges, especially given the specificities of each subproject and the limitations encountered. The relational dimension between advisors and student teachers was crucial, despite the virtuality causing some distancing. Digital mediation, while providing continuity to residency activities, was unable to fully replicate the authentic classroom experience. Remote teaching resulted in an artificialization of teacher learning, diverging from the program's purpose of providing a complete immersion in the teaching and learning process. The abrupt shift to remote teaching intensified emotional pressures and workload for advisors, negatively impacting teacher well- being, especially considering the transfer of teaching to the residential environment, bringing with it various demands that were previously separated. Initial guidance strategies focused on overcoming technological limitations and understanding the residents' scenario. The didactic movement of the advisors evolved into an approach adapted to remote teaching, incorporating inter-institutional exchange, resident engagement, and guidance based on reflection on distance learning. The results of this research contribute to understanding the experience of teaching advisors in the PRP, especially in the context of the COVID-19 pandemic. The findings point to the need to rethink initial teacher education to encompass the perspective of remote and hybrid teaching from the standpoint of teacher-educators, the advisors.